A method for analyzing the VSWR effects of paint on K-band onboard antenna arrays - Xianjin Yi (AIP Advances)
Today’s aerial vehicles are fitted with antennas for various wireless services, which are commonly designed as conformal surfaces. To improve the appearance of the finished aircraft, the antenna surfaces are painted. The paint on K-band antenna arrays leads to an offset of working VSWR (Voltage Standing Wave Ratio). This study explores a method for analyzing the VSWR effects of paint on K-band antenna arrays. First, we measured the VSWR results for both with and without paint on antenna. By comparing the VSWR results, the offset of working VSWR can be calculated. Then, the dielectric constant of the paint is estimated by simulation based on the offset of working VSWR. Finally, the effect of VSWR offset can be solved by considering the paint with simulation. As a sample, an antenna array working K-band is designed, fabricated, and measured. The VSWR results both with and without paint on antenna are compared.